The Effect of The Combination of Prenatal Yoga and Lavender Aromatherapy on The Sleep Quality of Third Trimester Pregnant Women at Puskesmas I Denpasar Selatan in 2022: The sleep quality of pregnant women: combination effect of prenatal yoga and lavender aromatherapy - Arini, Ketut Novia; Suarmini, Kadek Ayu (Bali Medika Jurnal, 2022)
Gangguan tidur dan kelelahan adalah kondisi yang paling sering dialami oleh ibu hamil. Sebesar 97% ibu hamil di Indonesia akan mengalami gangguan tidur pada usia kehamilan memasuki trimester ketiga. Beberapa alternatif terapi yang dapat memperbaiki kualitas tidur ibu hamil adalah dengan yoga dan aromaterapi. Dalam gerakan yoga terkandung efek relaksasi yang dapat menstabilkan emosi ibu hamil, sedangkan aromaterapi lavender memiliki senyawa sedative dan anti neurodepresive yang dapat memberikan efek rileks dan dapat mengatasi kesulitan tidur. Penelitian ini bertujuan untuk mengetahui pengaruh yoga prenatal yang dipadukan dengan pemberian aromaterapi lavender terhadap kualitas tidur ibu hamil trimester III. Penelitian ini menggunakan rancangan quasi eksperiment. Penelitian dilaksanakan di Puskesmas I Denpasar Timur pada bulan September-Oktober 2022. Teknik pengambilan sampel dalam penelitian ini secara accidental sampling. Jumlah sampel yang digunakan dalam penelitian ini adalah 30 responden. Dari hasil penelitian diperoleh bahwa sebagian besar ibu hamil berada pada rentang umur 20-35 tahun, sebagian besar ibu hamil termasuk dalam kategori multigravida dan hamper seluruh ibu hamil belum pernah melakukan yoga prenatal. Terdapat pengaruh yang signifikan dengan p < 0.05 dari pemberian yoga prenatal yang dipadukan dengan pemberian aromaterapi lavender terhadap peningkatan kualitas tidur ibu hamil trimester III. Diharapkan setiap tenaga kesehatan dapat memberikan pelayanan berupa yoga prenatal dengan pemberian aromaterapi lavender untuk mengatasi gangguan tidur pada ibu hamil.   Sleep disturbance and fatigue are conditions that are most often experienced by pregnant women. As much as 97% of pregnant women in Indonesia will experience sleep disturbances at the age of pregnancy entering the third trimester. Some alternative therapies that can improve the quality of sleep for pregnant women are yoga, aromatherapy, massage, acupressure and reflection. The yoga movement contains a relaxing effect that can stabilize the emotions of pregnant women, while non-pharmacological therapies that can be used to overcome sleep difficulties experienced by pregnant women are aromatherapy, one of which is lavender aromatherapy. Lavender aromatherapy has sedative and anti-neurodepressive compounds that can provide a relaxing effect and can overcome sleep difficulties experienced by third trimester pregnant women. This study aims to determine the effect of prenatal yoga combined with lavender aromatherapy on the sleep quality of third trimester pregnant women. This study used a quasi-experimental design that would directly measure changes in the sleep quality of respondents before and after being given treatment. The research was carried out at the East Denpasar Health Center I in September-October 2022. The sampling technique in this study was accidental sampling. The number of samples used in this study were 30 respondents who were divided into two groups, namely the treatment group and the control group. From the results of the study it was found that most pregnant women were in the age range of 20-35 years, most pregnant women were included in the multigravida category and almost all pregnant women had never done prenatal yoga. There was a significant effect with p <0.05 from giving prenatal yoga combined with giving lavender aromatherapy to improving the sleep quality of third trimester pregnant women. It is hoped that every health worker can provide services in the form of giving prenatal yoga combined with giving lavender aromatherapy to overcome sleep disturbances that are often felt by pregnant women in the third trimester.